Issues of Optimizing the Management System of Chemical Industry Enterprises (European Journal of Economics, Finance and Business Development, 2023)
The article describes the characteristics of optimization processes of chemical industry enterprises, the organization and stages of optimization work. The importance of optimization issues in improving the control system is described.